Reverse Tracking Graph Based on Dynamic Path Planning - Devanta Abraham Tarigan; Muhammad Zarlis; Rahmat Widia Sembiring (InfoTekJar : Jurnal Nasional Informatika dan Teknologi Jaringan, 2021)
This paper gives substance to Dynamic Path Planning focusing on reverse tracking method. The development of this method are proposed and expected to reduce the algorithm scanning the whole graph repeatedly. In this paper, several approachment will be presented sequentially. First, analysis and modeling of the obstacle and environment, pre-path planning, Depth First Search for availability path planning, and improvement of the Dijkstra algorithm for the shortest path. There-in the proposed model is defined by adopting the reverse feature in the Depth First Search algorithm in the finding of the availability path on the graph.